ФІСКАЛЬНЕ АДМІНІСТРУВАННЯ ПОДАТКОВОГО МЕХАНІЗМУ ПІВДЕННОЇ УКРАЇНИ (остання чверть XVIII ñ перша чверть XIX століття) (Zaporizhzhia Historical Review, 2021)
The fiscal management in the Southern Ukraine during the last quarter of the 18th ñ the first quarter of the 19th cen. is the subject matter of analysis in the article. The author states that the fiscal policy of the Russian government based on the compromise between the requirements of the local social groups and the interests of the state. It is proved that the fiscal management in Southern Ukraine during the target period was not stable and uniform.